Electronic Spectral Characterization of Sulphonanilides with Pr(III) and Nd(III) Ions. - PANDEY, H.K.; CHAWLA, GOURAV; GAKHAR, SEEMA (Asian Journal of Chemistry, 2010)
The Pr(Ill) & Nd(III) doped systems with various sulphonanilide ligands have been studied with respect to electronic spectral parameters. Different parameters prove the covalent nature of M—L bond instead of ionic bond.